Dobutamine and cardiac index change in fluid-refractory children with septic shock - Mejestha Rouli Puspitasari; Dewi Ratih Priyantiningsih; Adhie Nur Radityo (Indonesian Pediatric Society, 2026)
Background Sepsis became the main cause of morbidity and mortality in children globally. The mortality rate was 18-46% in developing countries. The primary goal of septic shock resuscitation was to achieve adequate cardiac output (CO), which 18% responded to fluid resuscitation and needed vasoactive therapy. Dobutamine as inotrope and vasodilator agent could increase CO that measured by cardiac index (CI). Its heterogeneity variance response was influenced by many factors. Objective To analyze the effectiveness of dobutamine administration at 5 mcg/kg/minute on CI change in fluid-refractory children with septic shock and identify factors to improve outcomes in children with septic shock. Methods This pretest and posttest study included 50 children aged 1 month to < 18 years who were diagnosed with fluid-refractory septic shock and admitted to the pediatric intensive care unit (PICU) at Dr. Kariadi Hospital, Semarang, during the period of January 2022 to December 2023. The CI, corrected flow time (FTc) (preload), Smith-Madigan inotrophy index (SMII) (contractility), and systemic vascular resistance index (SVRI) (afterload) parameters were measured by an ultrasonic cardiac output monitor (USCOM) before and after dobutamine administration at 5 mcg/kg/minute. T-paired and Chi-square tests were used to analyze data. Results After dobutamine administration at 5 mcg/kg/minute, CI increased in 54% of subjects, with mean delta of 0.45 (SD 1.17 L/min/m2; P: 0.008) and low SMII was associated with an increased CI (PR: 8.944 (95%CI: 2.314 to 34.581; P: 0.001). Age, sex, nutritional status, anemia, acute kidney injury, total fluid resuscitation, FTc, and SVRI did not significantly affect CI change. Conclusion Dobutamine at 5 mcg/kg/minute had an effect of increasing CI, especially in patients with low SMII in fluid-refractory septic shock.